Error estimators for a mixed method - Alonso, Ana Esther (1996)
We present two a-posteriori error estimators for elliptic partial differential equations, when we use a mixed method. One is based on a adequate evaluation of the residual of the finite element solution and the other on the solution of a local problem. We prove their equivalence with the norm of the error, when the data is locally smooth.